Thinking Marginally: Ethno-Historical Notes on the Nature of Smuggling in Human Societies - Tagliacozzo, Eric (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractThis essay examines a range of issues at stake in the transgression of political boundaries across a spectrum of human societies. The aim of the article is not to catalogue a vast series of boundary-crossing actions, but rather to suggest what some of the main characteristics and variables are of contrabanding across frontiers. An attempt will be made to briefly define the problem of illicit facilitation across borders, as different theorists have delineated this issue in different ways. A brief discussion will ensue on the nature of border space itself, as such spaces have been conceptualized by a range of scholars who have thought about this issue for quite some time. The nature of sources on this problem will be quickly interrogated, as the sources of reporting on illicit facilitation vary widely, and different sources impart divergent kinds of information on this topic. A brief foray into a few historical examples of cross-border facilitation will be provided, to show how contemporary contexts of this issue are connected (or sometimes disjointed) from similar notions in the past. I will then give some sense of the broad variety of global experiences of illicit facilitation, as this act is undertaken across the width and breadth of the planet on an everyday basis. I will conclude with a discussion of two interesting regional theatres – Africa and Southeast Asia – where some of these processes can be seen in more detail. I argue in this essay that it is only by looking at smuggling through a number of different vantages that we have any chance of describing this practice as a crucial component of the global political economy.